Physiological, Biochemical and Energetic Characteristics of Torulaspora globosa, a Potential Producer of Biofuel - Svetlana V. Kamzolova; Igor G. Morgunov (Energies, 2021)
It was obtained that the yeast Torulaspora globosa VKPM Y-953 is suitable for the production of biodiesel fuel. Zinc plays an important regulatory role in the metabolism of the studied strain. The study of the growth parameters and the fatty acid profile of the yeast T. globosa showed that the limitation of its growth by ethanol, at different concentrations of zinc in the medium, considerably influences the chemical composition and the energy content of yeast cells, but not their yield by weight (Yx/s). The increased concentrations of zinc in the medium, in combination with the yeast growth limitation by ethanol, elevated the content of lipids in the cells by 28% and diminished the content of proteins by 14%. At the same time, the limitation of yeast growth by zinc decreased Yx/s and energy (ηX/S) by 2.6 and 3.1 times, respectively. In this case, the content of lipids in cells fell by 72%, while that of proteins rose by 65%. The fatty acid profile of the T. globosa cells was used to estimate the main characteristics of biodiesel (iodine value, cetane number, density, and kinematic viscosity). The biomass of T. globosa can also be used in agriculture as a feed additive rich in essential amino acids.